Herdabilidade de traços relacionados a adiposidade, homeostase da glicose e perfil lipídico na população indígena xavante - Santos, Marcia Costa dos [UNIFESP] (2016)
Objective: Xavante Indians represent a genetically isolated group with high prevalence of obesity, type 2 diabetes and metabolic syndrome. The aim of this study was to characterize the lipid profile, investigate the genetic influence on traits related to adiposity, glucose homeostasis, and lipid traits, and to assess the pleiotropic relationship for lipid components in this Brazilian indigenous population. Design and Methods: The study population comprised 955 individuals whose heritage was full Xavante, aged 41.8 ± 19.2 years. The participants underwent clinical examination including the anthropometric measurements body mass index (BMI) and, waist and hip circumferences. Body fat was estimated by bioimpedance and body adiposity index (BAI). Plasma levels of fasting and 2-h glucose, fasting C-peptide, adiponectin, total cholesterol, LDL-c, HDL-c, VLDL-c, apolipoprotein A1 and apolipoprotein B were measured. Heritability (h2) for all traits and pleiotropy among lipids traits were performed by univariate and bivariate variance component analysis method (polygenic model), unadjusted and adjusted for age and sex, using the SOLAR software. Heterogeneity among sexes for heritability estimative was assessed in both models. Results: The prevalence of dyslipidemia, mainly due to low HDL-c or high triglycerides levels, was 77.5%; higher in men than women (82.7% vs. 72.5%, p=0.0002). ApoB/apoA-I ratio indicating elevated cardiovascular risk (defined as >0.9 for men and >0.8 for women) was observed in 15.9% of the studied subjects. Except for 2-h glucose, all other variables were significantly heritable. The traits with high or intermediate heritability estimates, under adjusted model, were waist circumference (0.55), BMI (0.49), total fat mass (0.45), hip circumference (0.46), BAI (0.36), total cholesterol (0.45) and LDL-cholesterol (0.36). Heritability estimates for glucose homeostasis variables were lower than for adiposity, ranging from 0.15 to 0.35. Women had greater h2 than men for BMI, BAI, total body fat mass, waist and hip circumference. High genetic correlations were observed between total cholesterol and LDL-c and apo B; between VLDL-c and apo B, triglyceride and total cholesterol; and between LDL-c and Apo B. Conclusions: In Xavante Indians, a high prevalence of dyslipidemia, mainly due to hypertriglyceridemia and low HDL-c was observed. We showed a significant genetic influence in traits related to adiposity and lipid profile. Glucose homeostasis variables are also heritable, although the genetic contribution is less pronounced. Pleiotropic relations were detected between some lipids components, suggesting that the same set of genes is regulating these traits.